Peningkatan Kemampuan Mengenal Konsep Ukuran Berat Benda melalui Media Timbangan pada Anak Kelompok B TK ABA Pengkol Sragen - Maryam, Siti (Universitas Pendidikan Indonesia Kampus Serang, 2022)
One of the cognitive learning that is important to develop is the ability to measure and early age is a potential time to develop it. The formulation of the problem in this study, namely how to improve the ability to recognize the concept of measuring the weight of objects through the medium of scales in Group B children of ABA Pengkol Kindergarten, Tanon District, Sragen Regency. The purpose of this study was to determine the increase in the ability to recognize the concept of measuring the weight of objects through the media of scales in group B children at ABA Pengkol Kindergarten, Tanon District, Sragen Regency. The subjects of this study were group B students of ABA Pengkol Kindergarten, Sragen Regency, with a total of 16 students consisting of 8 male students and 8 female students. In this classroom action research, the data collection techniques used were observation and documentation. According to the data obtained through pre-cycle observations, cycle I and cycle II, the increased ability was evidenced by the percentage of measurement activities showing an increase from before and after the action. Media scales can help understand the concept and practice of direct measurement for early childhood. So it is proven that learning to recognize the weight of objects with the media of scales can improve the ability of group B children in ABA Pengkol Kindergarten